Survey of plant hosts and natural enemies of two-spotted spider mite Tetranychus urticae Koch in some sites of Al -jabal Al-Akhdar region, Libya - A.Kelah, Ommran; H.Amin, A. (Al-Mukhtar Journal of Sciences, 2005)
In present study, the two-spotted spider mite, Tetranychus urticae Koch was recorded on 23 host plants in some sites of Al - Jabal Al - Akhdar region , Libya , including 7 species of fruit trees , 10 species of vegetable crops , 2 species of field crops , 2 species of ornamental plants and one species of wild plant . Also 9 species of natural enemies were recorded on T. urticae, including 6 species of predaceous insects, 2 of them belong to the family Coccinellidae , 2 species of family Anthocoridae, one species of family Chrysopidae and one species of family Thripidae, in addition to the 3 species of predaceous mites belonging to the family Phytoseiidae , including: Amblyseius swiriski A.- H. Neoseiulus cucumeris (Zhanga ) and Neoseiulus steulus Fox .